PRODUCTION OF PATHOGENESIS RELATED PROTEINS IN TOBACCO PLANTS SYSTEMICALLY INFECTED WITH EGGPLANT MOTILE POTYVIRUS - A. VARMA, M. CHANDRA SEKHAR, P. USHA SARMA, A. P. JOSHI, M. RAJAMANNAR AND (Indian Phytopathology, 2002)
Infection of Nicotiana tabacum cv. Xanthi-nc with, eggplant mottle potyvirus resulted in production of acidic, low molecular weight additional proteins which resemble the pathogenesis related proteins. One protein with pl 4,7 was found to be present in low amounts in healthy plants and had five times more concentration in diseased plants. Three other proteins with pl 3.5, 3.9 and 4.4 were found only in diseased plants. One of these additional proteins reacted strongly in Western blot after affinity purification and SOS-PAGE. A new immuno affinity purification method was developed for the purification of pathogenesis related proteins